Shared and task‐specific muscle synergies of Nordic walking and conventional walking. (3rd November 2017) - Boccia, G.; Zoppirolli, C.; Bortolan, L.; Schena, F.; Pellegrini, B.
Abstract : Nordic walking is a form of walking that includes a poling action, and therefore an additional subtask, with respect to conventional walking. The aim of this study was to assess whether Nordic walking required a task‐specific muscle coordination with respect to conventional walking. We compared the electromyographic (EMG) activity of 15 upper‐ and lower‐limb muscles of 9 Nordic walking instructors, while executing Nordic walking and conventional walking at 1.3 ms −1 on a treadmill. Non‐negative matrix factorization method was applied to identify muscle synergies, representing the spatial and temporal organization of muscle coordination. The number of muscle synergies was not different between Nordic walking (5.2 ± 0.4) and conventional walking (5.0 ± 0.7, P  = .423). Five muscle synergies accounted for 91.2 ± 1.1% and 92.9 ± 1.2% of total EMG variance in Nordic walking and conventional walking, respectively. Similarity and cross‐reconstruction analyses showed that 4 muscle synergies, mainly involving lower‐limb and trunk muscles, are shared between Nordic walking and conventional walking. One synergy acting during upper limb propulsion is specific to Nordic walking, modifying the spatial organization and the magnitude of activation of upper limb muscles compared to conventional walking. The inclusion of the poling action in Nordic walking does not increase the complexity of movement control and does not change the coordination of lower limb muscles. This makes Nordic walking a physical activity suitable also for people with low motor skill.